Policy-based customisation and corrective adaptation of composite web services. (27th October 2011) - Erradi, Abdelkarim
Due to the typical long-running character of business processes, it is often desirable to be able to change a running process to respond to changes of business requirements and company policies. However, current process orchestration engines do not provide the flexibility and dynamism needed to support ad hoc changes (e.g., add, shift or delete activities) to a pre-defined service composition in order to deal with an exceptional situation that may occur during process execution. In this paper, we advocate a policy-based framework to manage customisation and corrective adaptation of web services in a controlled and reliable way. WSPolicy4MASC language is used to define process-level adaptation requirements. The latter are enforced by manageable and adaptable service compositions (MASC) middleware both at creation time and during an instance's lifecycle. This paper presents MASC middleware prototype implementation and some experimental results showing the viability and scalability of our approach to providing adaptive services.